Bearing capacity of T-cross section piles in Sand = Nośność pali o przekroju teowym w piaskach - Malyshev, Oleg (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper describes a series of pile tests in sand. T-cross and square cross section piles were jacking by static vertical load with a vibration. Special tests were carried out to examine the influence of T-cross section pile form on it bearing capacity, and the results of comparison bearing capacity on one cub meter of T-cross and square cross section jacking piles in the same ground conditions are described. The jacking vertical static load, sizes of displacements and compaction zones of a ground around a shaft of the experienced piles were investigated.
Keywords: pile; cross section; bearing capacity; field tests; sandy soil; precast concrete; compaction zones; jacking; pal; przekrój teowy; nośność; badania polowe; gleby piaszczyste